The role of communication activities of chambers of commerce in the Eastern Province in shaping companies’ awareness of the services provided: a survey study (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to evaluate the role of communication activities carried out by the chambers of commerce in the Eastern Province (Asharqia Chamber, AlAhsa Chamber, Hafar AlBatin Chamber) in shaping companies’ awareness of the services provided. The study relied on the descriptive analytical approach using a questionnaire for a random sample of 384 companies out of 150,000 companies. The results showed a strong positive relationship between chambers of commerce's communication activities and companies' level of awareness of available services. The most effective communication channels were social media, workshops, and exhibitions, reflecting the importance of these methods in reaching companies and influencing their awareness of services. The study revealed that most companies found the information provided by the chambers clear and comprehensive, with a small percentage facing challenges in accessing this information. The study also revealed varying levels of companies' use of the services, with a high percentage confirming they benefited greatly from the services provided by the chambers of commerce. The study recommended increasing investment in digital tools, increasing the number of specialized workshops and seminars, and developing the website to make it more accessible and interactive. It also called for launching periodic awareness campaigns and customizing communication content to suit the needs of different companies. It also called for periodically evaluating the effectiveness of these activities to enhance their impact on companies' awareness of the services provided.
Keywords: Chambers of Commerce; Companies; Communication Activation; Region; Customer Satisfaction in the Eastern Province; Marketing; Awareness